Profitability as a Moderator in the Implementation of Environmental Management Accounting for Corporate Sustainability - Ria Meilan; Een Yualika Ekmarinda; Ikhwanul Hakim (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
This study aims to examine the effect of implementing environmental management accounting on corporate sustainability moderated by company profitability in mining and manufacturing companies listed on the Indonesia Stock Exchange from 2019-2022. Environmental management accounting is measured by eco-efficiency, and company sustainability is measured by GRI standards using content analysis with a scoring approach in assessing environmental and social achievements. Profitability is measured by return on equity (ROE). This research uses a panel data method with a fixed effect model approach. The sampling technique was purposive sampling with the criteria of companies that publish annual reports, and disclose sustainability reporting successively during the 2019-2022 period so that a total of 33 companies were obtained. The research results show that there is a positive influence on the application of environmental management accounting on corporate sustainability strengthened by profitability as a moderator. The application of environmental management accounting can increase its influence on corporate sustainability when the company's profitability is high. This condition is expected to have an impact on achieving corporate sustainability by fulfilling economic, environmental, and social aspects by the triple bottom line concept as a pillar that can create a sustainable business.